A thermodynamic and kinetic study of the antioxidant activity of natural hydroanthraquinones. Issue 34 (27th May 2020) - Vo, Quan V.; Thong, Nguyen Minh; Le Huyen, Trinh; Nam, Pham Cam; Tam, Nguyen Minh; Hoa, Nguyen Thi; Mechler, Adam
Abstract : Novel hydroanthraquinones isolated from Talaromyces islandicus EN-501 exhibited promising antioxidant properties in preliminary studies, raising the prospect of adapting these compounds for therapeutic use in diseases caused by oxidative stress. Abstract : Novel hydroanthraquinones isolated from marine algal-derived endophytic fungus Talaromyces islandicus EN-501 exhibited promising antioxidant properties in preliminary studies, raising the prospect of adapting these compounds for therapeutic use in diseases caused by oxidative stress. For medicinal applications it is beneficial to develop a full understanding of the antioxidant activity of these compounds. In this study, the hydroperoxide radical scavenging activity of five natural hydroanthraquinones was evaluated by kinetic and thermodynamic calculations. The results showed that the radical scavenging of these hydroanthraquinones in the gas phase and in lipid solvents was defined by the formal hydrogen transfer mechanism, that for the polar environments was decided by the sequential proton loss electron transfer pathway. The hydroanthraquinones exhibited good hydroperoxide scavenging activity in both polar and non-polar media. The overall rate constant values for the radical scavenging reaction were in the range of 3.42 × 10 1 to 2.60 × 10 5 M −1 s −1 and 3.80 × 10 6 to 5.87 × 10 7 M −1 s −1 in pentyl ethanoate and water solvents, respectively. Thus the activity of 8-hydroxyconiothyrinone B (1 ) is about 2.6 and 444.6 times higher than that of Trolox in the studied solvents, identifying 8-hydroxyconiothyrinone B as a promising antioxidant.